DEVELOPMENT OF MULTI MEDIA-BASED LEARNING CAMTASIA IN SMP MUHAMMADIYAH 1 AND 57 MEDAN - Harahap, Mukti Hamjah; Husrizalsyah, Dedi; Fitrawaty, Fitrawaty (Journal of Community Research and Service, 2017)
Abstract Increased ability of teachers to develop multi-media learning media in particular is a demand professionalism of teachers today. The success in the learning process in the classroom can not be separated from the ability of teachers in designing learning. But in the first SMP Muhammadiyah only one teacher who can design using multi-media learning. Therefore, the learning process is perceived by the students become monotonous. Through science and technology program for the Community (IbM), Institute of Community Services team at Medan State University conduct training activities for teachers in designing multi-media-based learning using Camtasia. Coaching is done using the method of training and mentoring oriented instructional design project each teacher trainee. The success of the activities is based on an indicator of increased teacher's knowledge-based multi-media Camtasia, project success rate, and the impact felt by the students. Once the activity is completed, the resulting increase in teachers' knowledge gained an average of 40%, while the completeness projeknya is 13 out of 14 participants. While the results projeknya still vary from the simplest to the project that is almost perfect. The impact is felt by students when projeknya used in the learning process 93% of students said he was happy to learn by using multimedia. Keywords: Multi Media, Devotion, Indicators.